Policewomen who made history: breaking through the ranks - Snow, Robert L. (Rowman & Littlefield Publishers, 2010)
The moment -- History of women in policing, 1845-1968 -- Motivations -- Car 47 -- Reaction to the advancement of policewomen -- Heroines in the struggle for equality -- Policewomen after Car 47 -- Strain on relationships -- The supreme sacrifice -- Women in other public safety jobs -- Policewomen today and tomorrow